2011
DOI: 10.1007/s00425-011-1446-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of xylanase-induced nitric oxide and phosphatidic acid production in tomato cells

Abstract: The second messenger nitric oxide (NO), phosphatidic acid (PA) and reactive oxygen species (ROS) are involved in the plant defense response during plant-pathogen interactions. NO has been shown to participate in PA production in response to the pathogen-associated molecular pattern xylanase in tomato cell suspensions. Defense responses downstream of PA include ROS production. The goal of this work was to study the signaling mechanisms involved in PA production during the defense responses triggered by xylanase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Zymogram analysis as well as Congo red staining of the inoculated birch wood xylan agar plate revealed that the necrotrophic fungus M. phaseolina could produce highly active extracellular xylanase (Figure 7D). In fact, xylanase is known to play a vital role in presenting pathogen associated molecular pattern (PAMP) which is evident in different model systems [20], [21]. In tomato cells, NO has been shown to be involved in the induction of phosphatidic acid (PA) production in response to the PAMP xylanase [22].…”
Section: Resultsmentioning
confidence: 99%
“…Zymogram analysis as well as Congo red staining of the inoculated birch wood xylan agar plate revealed that the necrotrophic fungus M. phaseolina could produce highly active extracellular xylanase (Figure 7D). In fact, xylanase is known to play a vital role in presenting pathogen associated molecular pattern (PAMP) which is evident in different model systems [20], [21]. In tomato cells, NO has been shown to be involved in the induction of phosphatidic acid (PA) production in response to the PAMP xylanase [22].…”
Section: Resultsmentioning
confidence: 99%
“…Phosphatidic acid (PA) is an abundant membrane phospholipid increasingly recognized as a signaling intermediate during innate immunity (Zhao, 2015). In rice (Oryza sativa) and tomato (Solanum lycopersicum) suspension-cultured cells, PA accumulates within a few minutes upon treatment with various MAMPs (van der Luit et al, 2000;Yamaguchi et al, 2003Yamaguchi et al, , 2005Bargmann et al, 2006;Laxalt et al, 2007;Lanteri et al, 2011;Raho et al, 2011). Nod factors have also been reported to induce PA production in vivo (den Hartog et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, modulation of a central MAPK cascade may converge both H 2 O 2 and NO signaling pathways activated in response to pathogen infection. In tomato cell suspensions, upon xylanase perception, cells activate a protein kinase pathway required for NO formation and S -nitrosylation-dependent mechanisms which are involved in downstream signaling, leading to production of polyamine and ROS production (Lanteri et al, 2011). …”
Section: Ros and No Signaling In The Hypersensitive Responsementioning
confidence: 99%